2017
DOI: 10.1111/ceo.12927
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for radiation‐induced optic neuropathy: a case–control study

Abstract: Importance Identifying risk factors for RION could promote a more conservative approach to radiation treatment planning in vulnerable patients. Background This study explored possible factors beyond radiation dose associated with the development of radiation-induced optic neuropathy (RION) after external beam radiation therapy. Design This was a retrospective case-control study conducted at a university hospital tertiary care center. Participants Cases (n=14) meeting criteria for a diagnosis of RION by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Ozkaya et al ( 33 ) found that VF and contrast sensitivity were significantly affected with a mean dose of more than 50 Gy in NPC patients. According to Ferguson ( 34 ), no significant correlation for other risk factors was identified in RON when a lower radiation dosage was applied in EBRT. The mean dose of our patients reached ~65 Gy, much higher than the threshold presented by Ozkaya.…”
Section: Discussionmentioning
confidence: 99%
“…Ozkaya et al ( 33 ) found that VF and contrast sensitivity were significantly affected with a mean dose of more than 50 Gy in NPC patients. According to Ferguson ( 34 ), no significant correlation for other risk factors was identified in RON when a lower radiation dosage was applied in EBRT. The mean dose of our patients reached ~65 Gy, much higher than the threshold presented by Ozkaya.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the single-fraction dose can be beneficial for NOS repair ( 38 ). The partial volume effect and single-fraction irradiation dose to the NOS have been considered vital determinants of RION development ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of retinal metastases are treated with observation or radiotherapy [11,12]. However, local therapy with radiation is limited when the metastatic lesion involves the peripapillary retina because of the high risk of damaging the optic nerve [15][16][17].…”
Section: Discussion/conclusionmentioning
confidence: 99%